Environmental Impact of Slaughterhouse Waste and Technology-Based Processing Solutions: Dampak Lingkungan Limbah Rumah Potong dan Solusi Pengolahan Berbasis Teknologi - Suryono, Suryono; Rama, Bayu (Buletin Peternakan Tropis, 2025)
Slaughterhouses (RPH), where animals are processed for meat, generate various types of waste including blood, animal feces, and remnants from meat cutting. If not managed properly, these waste products can lead to serious environmental problems such as pollution of water, air, and soil, along with adverse effects on human health and ecosystems. The aim of this paper is to explore and assess the environmental impacts resulting from slaughterhouse operations and to identify eco-friendly technologies for managing this waste. This article examines the different types of waste generated during animal processing, evaluates the environmental consequences, and presents technological solutions that can help mitigate these issues. Techniques such as biogas production, anaerobic treatment of wastewater, and conversion of solid waste into valuable products are discussed as effective methods to minimize negative effects and enhance the sustainability of slaughterhouse operations. Implementing these technology-driven waste management approaches is crucial for achieving long-term environmental and economic benefits.